Analisis Laporan Keuangan Menggunakan Metode Vertikal dan Metode Horizontal terhadap Kinerja Keuangan pada PT. XYZ Periode 2019 – 2023 - Iqlima Irwanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
XYZ is a company engaged in the food and beverage industry and the beauty care industry. As a company included in the Indonesia Stock Exchange (IDX) that produces and distributes primary goods to consumers, PT. XYZ has intense competition with other companies in the same industry in marketing its superior products to consumers. Therefore, the company must know the growth of its financial performance has been in good condition from year to year in order to survive in the business world, by analyzing the annual financial statements. The data collection technique in this study uses documentation studies with secondary data collection obtained from the official website of the Indonesia Stock Exchange by applying non-statistical quantitative research methods and analyzing using vertical methods and horizontal methods. The analysis results obtained, both using the vertical method and the horizontal method, show fluctuating movements from 2019 to 2023. However, the company's financial performance can be assessed in good condition, because the company is able to increase its assets and profits in a positive trend when expenses for payment of liabilities and expenses have increased.